If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = -3(2x + 3) + 7x Reorder the terms: 16 = -3(3 + 2x) + 7x 16 = (3 * -3 + 2x * -3) + 7x 16 = (-9 + -6x) + 7x Combine like terms: -6x + 7x = 1x 16 = -9 + 1x Solving 16 = -9 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 16 + -1x = -9 + 1x + -1x Combine like terms: 1x + -1x = 0 16 + -1x = -9 + 0 16 + -1x = -9 Add '-16' to each side of the equation. 16 + -16 + -1x = -9 + -16 Combine like terms: 16 + -16 = 0 0 + -1x = -9 + -16 -1x = -9 + -16 Combine like terms: -9 + -16 = -25 -1x = -25 Divide each side by '-1'. x = 25 Simplifying x = 25
| Y=x^3-2 | | 38-3x=52+x | | -8+10x=102 | | c=23.14r | | 3(3n+3)=6(4n+2)+8 | | 6n-11=4n+5 | | 60-4x=14x+18 | | 7t+5(1-5t)= | | 7v=(9v-3) | | q=3h+3w | | 5x-5=-35 | | x+45=2x+25 | | 25x^2-8x+1=-18x | | 6(x+2)-4=10 | | 7(x+2)-(8n+6)= | | 4+9p-1=9p+21-3p | | 7x+7(-2x-3)=-22-6x | | 5x+6=2x+9 | | w=21+2w | | 3(x+3)=39 | | 5x-4=50x+14 | | (2x-5)=11 | | 2-4+10=2x-6[3x-4] | | 9x^2-8x+4=-20x | | 100+12h=23h | | 2x^3+250x^12= | | 3x(4+9)= | | 14x=14000 | | -3(10m)(2p)= | | 40=2x+2 | | 4-8x=13+3x | | 4x+13=2x+7 |